Pemanfaatan Pekarangan Sekolah untuk Membuat Vertikultur Garden Tanaman Hias Krokot Merah dengan Menggunakan Botol Bekas - Darman Syafe’i; Firnawati Sakalena; Mauidotul Malikhah; Salsa Nadillah; Indiana Indiana; Puja Dwi Putri (CV. Aksara Global Akademia, 2025)
Verticulture is a way of farming or farming using planting media in containers arranged vertically (in tiers) to utilize the school yard.Verticulture can also be interpreted as a cultivation mechanism in a multi-level agricultural system with limited types of agricultural land available in the school area, so that planting using verticulture can be a solution for children in MI. The aim of verticulture is to get around the limited land in the school area, so that people who do not have land or land can still be productive in the agricultural sector.